PENGARUH PEMBERIAN KRIM EKSTRAK BUAH DELIMA (PUNICA GRANATUM L.) TERHADAP JUMLAH KOLAGEN: Studi Eksperimental Pada Tikus Jantan Galur Wistar Yang Dipapar UVB - Anneta Aulia Ismail; Chodidjah; Eni Widayati; Widiana Rachim (Jurnal Riset Multidisiplin Edukasi, 2025)
Ultraviolet B (UVB) exposure can trigger oxidative stress, DNA damage, and decreased collagen synthesis through the activation of inflammatory pathways and degradation of the extracellular matrix. Collagen is the main component of the dermis that maintains skin strength and elasticity, so its damage accelerates skin aging. Pomegranate (Punica granatum L.) contains bioactive compounds such as punicalagin, polyphenols, and ellagic acid, which have antioxidant and anti-inflammatory effects and support collagen regeneration by protecting fibroblasts from oxidative stress and suppressing the expression of collagen-degrading enzymes. This study aimed to determine the effect of pomegranate extract cream on collagen levels in male Wistar rats exposed to UVB. This study was an experiment with a post-test only control group design using 25 rats divided into five groups: normal control (K1), negative control (K2), positive control (K3), treatment 1 (K4), and treatment 2 (K5). The study lasted 14 days, including 7 days of adaptation, 7 days of treatment (UVB exposure and cream application), skin tissue collection, paraffin preparation, and histopathological observation with a 400x magnification microscope. The mean collagen counts for K1-K5 were 52.21 ± 6.40; 0.00 ± 0.00; 57.35 ± 6.20; 57.75 ± 7.27; and 61.30 ± 4.16, respectively. The Kruskal Wallis test showed significant differences between groups (p = 0.007). The Mann-Whitney test showed that K2 was significantly different from K1, K3, K4, and K5 (p = 0.005), while K1, K3, K4, and K5 were not significantly different. This study shows that the application of pomegranate fruit extract cream (Punica granatum L.) has an effect on collagen levels in male Wistar rats exposed to UVB.